Performance Analysis of Carded Silver System: A Case Study: Optimizing system availability through performance analysis of carded silver system (Journal of Advances and Scholarly Researches in Allied Education, 2019)
ReliabilityAvailability engineering is the vital upcoming field taken up by industries, engineers and research aspirants in today’s scenario.It affects all state of our life directly or indirectly. A performance model has been developed by considering the exponential distribution of probable failure and repair rate using Markovian approach. The differential difference equations for various state probabilities have been derived from state transition diagram and solved by applying differential equations to obtain the steady state system availability. In the current article, we perform the availability analysis of serial procedures on the carded silver production systemthe availability of the system is then optimized with the help of genetic algorithm (GA) technique. MATLAB 7.4 is used for the analysis of the system. The findings of the paper might be helpful for maintenance planning and identification of criticalsubsystem of the system.